Laparoscopic Complete Excision of the Posterior Muscular Cuff: Technique Refinements and Comparison With Stepwise Gradient Muscular Cuff Cutting for Hirschsprung Disease - Zheng, Zebing; Jin, Zhu; Gao, Mingjuan; Tang, Chengyan; Huang, Lu; Gong, Yuan; Liu, Yuanmei (Frontiers in Pediatrics, 2022)
Objectives Our institution had modified the Soave pull-through procedure using laparoscopic stepwise gradient muscular cuff cutting (LSGC) for Hirschsprung disease (HSCR). However, we found that a few children still suffered from obstructive symptoms and enterocolitis during the follow-up. Previous studies suggested that these symptoms might be caused by the retained muscular cuff. The purpose of this study was to employ a modified procedure of laparoscopic complete excision of the posterior muscular cuff (LCEPC) for HSCR and compare it with the laparoscopic stepwise gradient cutting muscular cuff (LSGC) procedure. Methods Our institution records of 83 patients with classic form HSCR who underwent LSGC or LCEPC between August 2014 and July 2018 at the Pediatric Surgery Department of Zunyi Medical University (Zunyi, China) were carefully reviewed (LSGC, n = 52; LCEPC, n = 31). In the present study, we compared the postoperative complications and defecation functions of the two groups. All patients were followed-up (1–5 years, with an average of 2 years). Results There were no differences regarding the operation time and the length of hospitalization between groups, while the anal dissection time in the LCEPC group (22.4 ± 4.8 min) was shorter than that of the LSGC group (45.5 ± 7.5 min) (p < 0.001). The postoperative complication of soiling was significantly increased in six patients (19.4%) in the LCEPC group compared with two patients (3.8%) in the LSGC group (p = 0.021). However, the total incidence of enterocolitis (two patients, 6.5%) was significantly decreased in the LCEPC group compared with the LSGC group (12 patients, 23.1 %) (p = 0.050). For anastomotic stricture, muscular cuff infection, and constipation, there were no significant differences between the two groups. No patients experienced bladder paralysis and incontinence postoperatively in this study. Anorectal manometries presented that the anorectal resting pressure was significantly lower in the LCEPC group (14.8 ± 2.7 mmHg) than the LSGC group (22.0 ± 3.8 mmHg), (p < 0.001). Conclusion The laparoscopic complete excision of the posterior muscular cuff method was demonstrated as safe and efficient, with a decrease in the incidence of enterocolitis, although it may increase the number of soiling incidents in the short period post-surgery owing to a dissected partial internal anal sphincter.